2019
DOI: 10.4236/ijcm.2019.102009
|View full text |Cite
|
Sign up to set email alerts
|

The Common Causes of Irritable Bowel Syndrome (IBS) in Northern Saudi Arabia

Abstract: Background: Several psychological factors have been linked to the etiology of irritable bowel syndrome (IBS). The aim of the present study was to assess the burden of psychological factors (anxiety, depression, and working status) in the etiology of IBS in Northern Saudi Arabia. Methodology: Data regarding IBS were attained from 930 Saudi volunteers existing in the city of Hail, Northern Saudi Arabia. A purposeful questionnaire was developed and used to obtain the required data. Each questionnaire was complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Although the percentage appeared to be significantly higher than the global prevalence of 3.8% (using Rome IV criteria) [11], our findings were equivalent to the reports conducted in the Middle East region. For instance, in Saudi Arabia, the prevalence ranged between 8.9%-40.7% and 31.3% [19]. A cross-sectional study on university students in Syria revealed a prevalence of 17% (using Rome III criteria) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although the percentage appeared to be significantly higher than the global prevalence of 3.8% (using Rome IV criteria) [11], our findings were equivalent to the reports conducted in the Middle East region. For instance, in Saudi Arabia, the prevalence ranged between 8.9%-40.7% and 31.3% [19]. A cross-sectional study on university students in Syria revealed a prevalence of 17% (using Rome III criteria) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted in Saudi Arabia found that lack of sleep, the use of certain medications, the consumption of caffeinated beverages, and working long hours all influence the occurrence of migraine [ 32 ]. Another study conducted in Saudi Arabia's northern region discovered that anxiety, depression, demanding professions, and excessive work hours are all attributed to IBS [ 33 ]. Further investigation is necessary to polish the factors influencing the high prevalence of migraine and IBS in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…In Northern Saudi Arabia, a lot of psychological factors were found to be associated with the analysis of Irritable Bowel Syndrome (21). In the study done by Alharbi, he stated that the possibility of anxiety as a factor of IBS was analytically significant as well as the risk of emotional stress.…”
Section: Occupational Stressmentioning
confidence: 99%